2011
DOI: 10.1097/inf.0b013e3181ff64ec
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Correct Parenteral Antibiotic Initiation and Outcomes From Severe Bacterial Community-acquired Pneumonia in Children

Abstract: In our critically ill children with severe bacterial CAP, longer delays in receipt of appropriate empiric antibiotics were independently associated with adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…34 it has recently been demonstrated that delays in the appropriate choice and dose of antimicrobials in critically ill children with severe bacterial community-acquired pneumonia lead to longer durations of mechanical ventilation, icU lengths of stay and hospital lengths of stay. 35 Prolonged infusions of β-lactams have been found to increase the probability of attaining bactericidal activity by prolonging the time to reach maximum concentrations, thereby increasing ft>mic. 11,21,36 in clinical practice, prolonged infusions have also demonstrated decreased mortality rates in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…34 it has recently been demonstrated that delays in the appropriate choice and dose of antimicrobials in critically ill children with severe bacterial community-acquired pneumonia lead to longer durations of mechanical ventilation, icU lengths of stay and hospital lengths of stay. 35 Prolonged infusions of β-lactams have been found to increase the probability of attaining bactericidal activity by prolonging the time to reach maximum concentrations, thereby increasing ft>mic. 11,21,36 in clinical practice, prolonged infusions have also demonstrated decreased mortality rates in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is critical because suboptimal anti-infective therapy is associated with worse outcomes. 6,[33][34][35][36][37][38][39] Systematic research using ex vivo circuits, large animal models, and population pharmacokinetic studies are indicated to improve antimicrobial dosing regimens and, therefore, patient outcomes during ECLS and CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Italy in 2012, showed that intravenous administration of antimicrobials has several far-reaching effects on pediatric patients and treatment itself (10). In the opinion of child psychologists, parenteral route of administration is considered to be traumatic for the child, with more rapid appearance of adverse effects (11).…”
Section: Discussionmentioning
confidence: 99%